Milk processing and preservation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
ILCA offers a number of group training courses each year for African scientists in various areas of livestock research, production and utilization. To make training more effective and to assist in the development of in-country training programmes,...